Exploring the Local Potential of the Ngawonggo Partitraan Site: Integrating Ecotourism into Biology Education - Rachmawati, Rizqi Nur; Mulyani, Dita Tri; Rizkiyah, Fitri; Maulanid, Hanifah Eka (Jurnal Kajian Pendidikan IPA, 2025)
This research is a descriptive analysis study that aims to evaluate the local potential of the Ngawonggo Partitraan Site as a learning resource in biology learning at school. Data was collected using a descriptive analysis approach based on the results of interviews and literature review. The interview technique in this study used a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats) to identify the advantages and challenges in utilizing the site as teaching material. The results of the literature study, it is known that the Ngawonggo Partitraan Site is a natural historical area that holds significant local potential, especially in terms of biodiversity. The site has various types of high-level plants, medicinal plants, and unique and distinctive types of bamboo. This biodiversity can be utilized as contextual biology learning materials, relevant to the surrounding environment, and in line with curriculum development and 21st century learning needs. Utilization of this local potential is expected to improve the quality of learning and strengthen the link between science and cultural values and local wisdom. Key word: Biology Learning, Ecotourism, Local Potential, Ngawonggo Partitraan Site